Weather Impacts On Natural, Social And Economic System (WISE) Part II: Individual Perception of Climate Extremes in Italy - Marzio Galeotti; Alessandra Goria; Paolo Mombrini; Evi Spantidaki (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper focuses on the results of the research work carried out by Fondazione Eni Enrico Mattei (FEEM) within the WISE project. This project aims at investigating the effects and the impacts of extreme weather events, particularly very warm summers, mild winters and storms, on the socio-economic systems of European countries. The output consists of a series of empirical studies, both of quantitative and qualitative-descriptive nature. The work of FEEM in the WISE project covers the quantitative analysis of the impacts of climate extremes on the socio-economic system in Italy and the analysis of individuals' perception of climate extremes based on results from individuals' surveys. In this paper is considered the study of the perception of weather impacts through questionnaire survey to the general public. With regard to the individuals' perception survey, a sample of 300 individuals were interviewed by telephone: 150 extracted from the North of Italy and 150 from the South of Italy. Individuals were asked general questions about their perception of climate extremes, and about the impacts of weather extremes on their daily habits at work, at home, in their leisure activities, on their transport patterns, on their health and tourism choices.
Keywords: Q2; Q25; 330; Climate change; Weather extremes; Perception; Impacts; Klimawandel; Katastrophe; Italien; Wetter; Meinung